Komposisi Nutrisi Maggot Yang Dibudidaya pada Media Berbasis Limbah Telur Infertil dan Ampas Tahu - Rosyadi, Muhammad Amri; Purnamasari, Dwi Kusuma; Erwan, Erwan; Sumiati, Sumiati; Wiryawan, K.G.; Syamsuhaidi, Syamsuhaidi; Maslami, Vebera (LPPM Universitas Mataram, 2024)
This research aims to reveal information about the nutritional content of maggots cultivated using hatching egg waste as a feed medium. Carried out in two stages, the first stage involves rearing maggots using hatching egg waste and tofu dregs, while the second stage focuses on analyzing the nutritional content of maggots. The research involved five treatments and four replications, with controls P0 (100% tofu dregs), P1 (75% tofu dregs + 25% egg hatching waste), P2 (50% tofu dregs + 50% egg hatching waste), P3 (tofu dregs 25% + 75% egg hatching waste, and P4 (100% egg hatching waste). Each replication used one gram of BSF fly eggs, with tofu dregs and egg hatching waste being fed as much as 20 kg/biopond during rearing. The variables observed involved dry matter, ash content, crude fat, crude fiber, and crude protein. The results showed that P4 treatment produced maggots with the highest nutritional content, especially in terms of crude protein. In conclusion, the best food media was found in treatment P4, providing the potential to improve the nutritional quality of maggots as an alternative food source.